2004
DOI: 10.1007/s00421-004-1116-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermal manikins of different body shapes and size

Abstract: Differences between manikins may be present due to manikin body shapes (male versus female). In order to examine such differences a study was designed. Comparisons were carried out based on: (1) tight versus loose clothing; (2) serial versus parallel calculation models; (3) even versus uneven clothing (insulation) distribution; and (4) the effect of donning clothes. Differences were observed between female and male manikins depending on body shape. However, these differences were within the range that was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…Fan and Keighley (1991) reported that the surface insulation in ''still'' air decreases 25% with the environment temperature reducing from 20 to À20 1C. On the other hand, environmental humidity (Meinander et al, 2003), and the size and shape of the body (Kuklane et al, 2004) was found to have little effect on the surface insulation. Due to the variations in the so-called ''still'' air conditions, this value varies in the literature.…”
Section: Review Of Past Related Workmentioning
confidence: 95%
“…Fan and Keighley (1991) reported that the surface insulation in ''still'' air decreases 25% with the environment temperature reducing from 20 to À20 1C. On the other hand, environmental humidity (Meinander et al, 2003), and the size and shape of the body (Kuklane et al, 2004) was found to have little effect on the surface insulation. Due to the variations in the so-called ''still'' air conditions, this value varies in the literature.…”
Section: Review Of Past Related Workmentioning
confidence: 95%
“…The size of the manikin was identical with the study infants and the clothes were well-Wtted, strengthening the reliability of the study (Kuklane et al 2004). However, there are number of factors, that could not be taken into consideration in the evaluation of clothing insulation, such as variation in how well the clothes Wt diVerent infants, diVerent kinds of prams or whether the covers were tightly or loosely placed over the infant, the reduction in insulation of clothes that have been washed or wetted a lot as well as body movements (ISO 9920, 2007) and sleep posture (Wilson and Chu 2005).…”
Section: Limitationsmentioning
confidence: 99%
“…The tests on manikins required for human test planning were carried out earlier in this project and the results have been discussed elsewhere [9]. The data from the present study with some additional test conditions has also been used for validation of a checklist for assessment of cold related risk factors [10], thus linking the work to the Barents Interreg IIA [11] programme on risk assessment and management of cold related hazards in arctic workplaces.…”
Section: Thermprotect Projectmentioning
confidence: 99%
“…The activity level for ensemble C (CM) was reduced compared to the SZ condition by 20% by taking into account weight distribution (footwear weight) and effect of stiff and bulky clothes [7,14,15,16]. The effective clothing insulation (I cle ) was measured on the thermal manikin [1,9,12]. Walking speeds were chosen [17] so that the activity level at the chosen ambient condition would correspond to thermal neutrality according to IREQ [2] as was also done in the SZ project [18].…”
Section: Ensemble Choicementioning
confidence: 99%